2003
DOI: 10.1182/blood-2002-08-2560
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress inhibits adhesion molecule expression in vascular endothelial cells induced by coculture with smooth muscle cells

Abstract: Vascular endothelial cells (ECs), which exist in close proximity to vascular smooth muscle cells (SMCs), are constantly subjected to blood flow-induced shear stress. Although the effect of shear stress on endothelial biology has been extensively studied, the influence of SMCs on endothelial response to shear stress remains largely unexplored. We examined the potential role of SMCs in regulating the shear stress-induced gene expression in ECs, using a parallel-plate coculture flow system in which these 2 types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 58 publications
4
133
0
2
Order By: Relevance
“…This is supported by studies showing that increased adhesion molecule expression induced by coculturing HUVEC with smooth muscle cells was abolished when direct contact between the two cells was prevented. 45 It is also possible that activating signals that modulate the endothelial or hepatocyte phenotype are produced as a result of the close juxtaposition of cells in our coculture system. For example, it recently was demonstrated that significant synthesis of the coagulation factor FVIII by hepatocytes in culture only occurs in the presence of vWF derived from ECs.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by studies showing that increased adhesion molecule expression induced by coculturing HUVEC with smooth muscle cells was abolished when direct contact between the two cells was prevented. 45 It is also possible that activating signals that modulate the endothelial or hepatocyte phenotype are produced as a result of the close juxtaposition of cells in our coculture system. For example, it recently was demonstrated that significant synthesis of the coagulation factor FVIII by hepatocytes in culture only occurs in the presence of vWF derived from ECs.…”
Section: Discussionmentioning
confidence: 99%
“…A co-culture system was used to investigate the synergistic effects of advanced glycation end-products on intercellular-cellular interactions [93,94], creating a more realistic platform for atherosclerosis research. Chiu et al [95][96][97] developed an important EC-VSMC co-culture system in which ECs are not only in close proximity to VSMCs, but are also constantly subjected to shear stress. In this model, ECs and VSMCs are separated by a porous membrane, with only the ECs being subjected to flow conditions.…”
Section: Co-culture Model Under a Haemodynamic Environmentmentioning
confidence: 99%
“…Atheroprone flow decreases VSMC gene expression (a-SMA and myocardin) and induces a proinflammatory phenotype in ECs and VSMCs by upregulating expression of VCAM-1, IL-8 and monocyte chemoattractant protein-1 (MCP-1) [111]. Shear stress downregulates pathophysiologically relevant gene expression under EC-VSMC co-culture [95,97].…”
mentioning
confidence: 99%
“…In response to reduced distal arterial resistance and increase flow, such as is demonstrated in the response to even modest lower extremity exercise, wall shear stress becomes antegrade and laminar throughout the cardiac cycle, mimicking those characteristic of more proximal aortic segments. These distinct regional differences in hemodynamic influences may account for some component of the differential aneurysm risk noted between the thoracic and abdominal aortic segments (Dua and Dalman, 2010 As commented above, there are several work in the literature that show a correlation between very low shear stresses and the loss of permeability of the endothelial cell membrane (Helmlinger et al, 1991;Chiu et al, 2003). Studies have been the basis of an alternative, or even complementary, mechanism responsible for the origin of these aneurysms.…”
Section: Abdominal Aortic Aneurysmmentioning
confidence: 99%